Risk Management for 4-H Youth Development Work: Transportation - Stefanie Prevatt; Dale Pracht; Paula Davis; Janet Psikogios; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS)
This 3-page document is one in the series Risk Management for 4-H Youth Development Work. It describes the best practices and procedures for transportation to and from Florida 4-H activities. Written by Stefanie Prevatt, Dale Pracht, Paula Davis, Janet Psikogios, Marilyn Norman, Kate Fogarty, and Jean Hink and published by the UF/IFAS 4-H Youth Development Department, February 2018. http://edis.ifas.ufl.edu/4h298